Deteksi dan prevalensi fasciolosis pada sapi bali di Rumah Potong Hewan (RPH) Oeba Kota Kupang - Luh Putu Eka Damayanti; Julyanti Almet; Annytha Ina Rohi Detha (Jurnal Veteriner Nusantara, 2019)
Fasciolosis is well-known as a common parasitic disease in ruminants especially cattle caused by infection of Fasciola sp. such as F. gigantica and F. hepatica. In Indonesia, fasciolosis in cattle are mainly caused by F. gigantica. The prevalence of fasciolosis were 40-90%, in some areas inside Yogyakarta. in the slaughter houses in Jakarta, it reached 61.3%, 60% in Banda Aceh and 18.29% in Karengasem-Bali. Samples used in this study were livers of 64 bali cows. Sampling was carried out at Oeba slaughterhouse in Kupang City during the month of May-June 2016. The sample examinations were conducted at the Laboratory of Parasitology Faculty of Veterinary Medicine Universitas Nusa Cendana. The method done to diagnose fasciolosis was a postmortem examination on the liver. This research aimed to detect and determine the prevalence fasciolosis on Bali cattle in Oeba slaughter house in Kupang city. From 64 liver samples examined, 11 were positive fasciolosis. Results showed that the prevalence of liver fluke infections (F. gigantica) on bali cattle in cattle Oeba slaughter house, Kupang city was 17.19%.